Parametric studies and application of fibre reinforced elastomeric isolators to low-rise buildings. (December 2021) - Sistla, Saiteja; Mohan, S.C.
Abstract: Base isolation systems are efficient in decoupling the building from the ground during earthquakes, leading to a reduction in seismic demand to be experienced by the isolated building. Although Steel Reinforced Elastomeric Isolators (SREIs) have been proven to perform well under earthquakes, they are mostly applied to special buildings and are not a cost-effective solution for low-rise buildings in developing countries like India. Although there are existing studies on Unbonded Fibre Reinforced Elastomeric Isolator (UFREIs), effectiveness of alternative low-cost fibres was not studied. Hence, this paper focuses on parametric studies of UFREI systems with various locally available fibres. Initial dimensions of UFREI required for seismic isolation of a two storeyed framed building were approximated. For these specific dimensions, performance of UFREI numerical models with various low cost locally available fibres were studied and compared with high strength fibres by conducting parametric studies using ABAQUS. Interesting results obtained by varying the strength, thickness and number of fibre layers are discussed in detail. A new parameter, peak stress ratio ( S n ) was proposed which helps in deciding the type of fibre to be used in UFREI systems. Based on the observations from these studies, a suitable configuration of UFREI was proposed. Significant improvement in the seismic performance of the base isolated building was observed from the linear static and dynamic analyses.